Low-site versus traditional peritoneal dialysis catheterization: A meta-analysis - Gong, Lifeng (Medicine (Baltimore), 2020)
BACKGROUND: The objective of this study was to compare the complications of low-site peritoneal dialysis (PD) catheter placement and traditional open surgery in peritoneal dialysis catheter insertion. METHODS: The following databases were searched from inception to September 6, 2019: PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure, and Wanfang. Eligible studies comparing low-site PD catheter placement and traditional open surgery in peritoneal dialysis catheter insertion were included. The data were analyzed using Review Manager Version 5.3. RESULTS: Seven studies were included in the meta-analysis. A total of 504 patients were included in the low-site PD catheter placement group, and 325 patients were included in the traditional open surgery group. Compared with traditional open surgery, low-site PD catheter placement had a lower incidence rate of catheter displacement (odds ratios [OR] 0.11, 95% CI 0.05–0.22, P < .01) and noncatheter displacement dysfunction (OR 0.11, 95% CI 0.04–0.31, P < .01). However, there was no difference between the 2 catheter insertion methods concerning bleeding (OR 0.53, 95% CI 0.23–1.22, P = .13), PD fluid leakage (OR 0.40, 95% CI 0.15–1.10, P = .07), hypogastralgia (OR 0.95, 95% CI 0.32–2.80, P = .93), peritonitis (OR 0.70, 95% CI 0.32–1.54, P = .38), or exit-site and tunnel infections (OR 0.39, 95% CI 0.14–1.03, P = .06). CONCLUSION: Low-site PD catheter placement reduced the risk of catheter displacement and noncatheter displacement dysfunction and did not increase the risk of bleeding, PD fluid leakage, hypogastralgia, peritonitis, or exit site and tunnel infections. Additional large multicenter randomized controlled trials are needed to confirm these conclusions.